Equity offerings following the IPO theory and evidence - Welch, Ivo (Journal of Corporate Finance, 1996)
This paper presents an IPO signaling model in which some issuers signal their higher quality not only by underpricing their IPO more, but also by waiting more patiently before they sell the remainder of the firm in a seasoned equity offering (SEO). In contrast to earlier models, this model offers empirical predictions (including functional forms) on easily observable variables: the IPO underpricing, after-market returns (reflecting the issuer's actions), and the timing of the SEO. The paper can thus calibrate and better test the theory. The evidence is that [a] signaling high-quality issuers are worth 2–3 times more than non-signaling low-quality firms; [b] the market recognizes the true quality of a firm with probability 30% per year; and [c] patience (i.e. waiting for extra funding) costs issuers about 15% of their value each year.